The Effects of the COVID-19 Pandemic on Health and Well-Being of Children and Youth in Nova Scotia: Youth and Parent Perspectives - Hilary A. T. Caldwell (Frontiers Media S.A., 2021)
Objectives: The COVID-19 pandemic led to school closures, cancellations of major events, and loss of in-person social interactions for children and youth. These restrictions undoubtedly impacted the lives of children and youth. This study describes the well-being of children and youth in Nova Scotia during the COVID-19 pandemic and their thoughts and feelings about the return to school, from the perspectives of both youth and parents.Methods: A province-wide survey was conducted in August 2020 with parents of school-age children and youth and youth to measure youth well-being since the pandemic began.Results: Parents of children and youth in grades pre-primary to 12 (n = 699; 53% girls) and youth in grades 3–12 (n = 279; 69% girls) completed the online survey. Perceptions of parents about children's emotions during the pandemic were: bored, safe, lonely, happy, and anxious. Youth reported feeling bored, relaxed, depressed, safe, and worried. Sixty-three percent of youth and 72% of parents reported that they/their child felt they were missing important life events. Parents reported that being with parents, being physically active and being with friends made their child feel positive. Youth reported that being with friends, pets and watching TV made them feel good during this time. Seventy-six percent of parents and 62% of youth reported they/their child were getting more screen time than before the pandemic. With schools closed, participants most frequently shared that they missed friends and social interactions, in-person learning, and extra-curricular activities. Youth and parents expressed worries about COVID-19 outbreaks and related restrictions when schools re-opened to in-person learning.Conclusion: The well-being of children and youth in Nova Scotia was greatly impacted by the COVID-19 pandemic and related school closures in 2020. It is essential that pandemic recovery plans prioritize the health and well-being of children and youth.